2014
DOI: 10.1177/1533317514549411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Consumption on Cognition and Regional Brain Volumes Among Older Adults

Abstract: This study utilized data from the Framingham Heart Study Offspring Cohort to examine the relationship between midlife and late-life alcohol consumption, cognitive functioning, and regional brain volumes among older adults without dementia or a history of abusing alcohol. The results from multiple linear regression models indicate that late life, but not midlife, alcohol consumption status is associated with episodic memory and hippocampal volume. Compared to late life abstainers, moderate consumers had larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 75 publications
2
26
0
Order By: Relevance
“…For example, intracranial area and several regional brain volumes appear correlated with tests of premorbid and fluid intelligence and tests of visuospatial memory. Several studies that have examined these associations have shown conflicting results [145][146][147][148]. The collective findings of these studies, however, suggest that light to moderate alcohol consumption, particularly wine, is associated with both improved cognition and larger total brain volume, which may be reduced in individuals consuming heavier amounts of alcohol.…”
Section: Regional Brain Volumesmentioning
confidence: 77%
“…For example, intracranial area and several regional brain volumes appear correlated with tests of premorbid and fluid intelligence and tests of visuospatial memory. Several studies that have examined these associations have shown conflicting results [145][146][147][148]. The collective findings of these studies, however, suggest that light to moderate alcohol consumption, particularly wine, is associated with both improved cognition and larger total brain volume, which may be reduced in individuals consuming heavier amounts of alcohol.…”
Section: Regional Brain Volumesmentioning
confidence: 77%
“…Three questions were asked related to alcohol consumption during study examinations by a study physician . These included, “During the past year, how many 12‐ounce bottles, cans, or glasses of beer did you consume per week?,” “During the past year, how many 4‐ounce glasses of wine did you consume per week?”, and “During the past year, how many cocktails (eg, drinks containing 1–1.5 ounces of liquor) did you consume per week?” In this analysis, we transformed responses to the 3 questions above into a total quantity of alcohol consumed per day variable (grams per day).…”
Section: Methodsmentioning
confidence: 99%
“…Previous literature suggests that alcohol misuse patterns characterized by binge, heavy, harmful, or hazardous drinking patterns have been associated with executive dysfunction, reduced working memory, problem solving difficulties, and attention impairments (Grant 1987). These symptoms may be attributable to underlying changes to patterns of regional brain activation and reduced grey and white matter volumes (Beresford et al 2006; Downer et al 2015). Excessive drinking also exacerbates cognitive issues after a traumatic brain injury, as both pre- and post-injury alcohol use is negatively associated with different aspects of cognitive functioning, such as verbal learning and memory, processing speed, and executive function (Ponsford et al 2013).…”
Section: Drug and Alcohol Abusementioning
confidence: 99%